Semantic relations and the lexicon : - Murphy, M. Lynne. (Cambridge University Press, 2003)
This book explores how some word meanings are paradigmatically related to each other, for example, as opposites or synonyms, and how they relate to the mental organization of our vocabularies. Traditional approaches claim that such relationships are part of our lexical knowledge (our "dictionary" of mentally stored words) but Lynne Murphy argues that lexical relationships actually constitute our "metalinguistic" knowledge. The book draws on a century of previous research, including word association experiments, child language, and the use of synonyms and antonyms in text.